The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1177/0892705717734607
|View full text |Cite
|
Sign up to set email alerts
|

The influence of skin-core residual stress and cooling rate on the impact response of carbon fibre/polyphenylenesulphide

Abstract: This study investigates the influence of macroscale skin-core residual stress and cooling rate on the impact response of aerospace grade carbon fibre/polyphenylenesulphide (CF/PPS). Numerical simulations are developed which analyse the thermal shrinkage and residual stress development of unidirectional (UD) lay-up configurations. Macroscale skin-core residual stresses are then incorporated into low-velocity impact simulations based on an orthotropic elastic material model. Interlaminar delamination is modelled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Yao et al 14 concluded that a low cooling rate improved the crystallinity and the strength of the single-lap joint of the CF/PEEK composites. McCallum 15 studied the influence of macroscale skin-core residual stress and cooling rate on the impact response of aerospace grade CF reinforced polyphenylene sulfide (CF/PPS). Fast-cooled laminates were shown to have a lower delamination extent when compared to slow-cooled laminates attributed to the faster cooling rate and the associated higher strain energy release rate.…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al 14 concluded that a low cooling rate improved the crystallinity and the strength of the single-lap joint of the CF/PEEK composites. McCallum 15 studied the influence of macroscale skin-core residual stress and cooling rate on the impact response of aerospace grade CF reinforced polyphenylene sulfide (CF/PPS). Fast-cooled laminates were shown to have a lower delamination extent when compared to slow-cooled laminates attributed to the faster cooling rate and the associated higher strain energy release rate.…”
Section: Introductionmentioning
confidence: 99%
“…The high-speed shear flow in the injection molding process makes the molecular chains of the sub-skin layer close to the mold surface highly oriented, and the relaxation of the molecular chains is limited by the core with a lower degree of orientation, resulting in residual stresses of skin stretching and core compression. 26 The shearing induced residual stress is of great significance for co-injection, 27 three-dimensional printing, 28 and surface wrinkle patterns. 29,30 However, the effect of viscoelasticity of triblock copolymer blends on molecular chain orientation and relaxation is rarely studied, and it is difficult to evaluate the shear-induced residual stress.…”
Section: Introductionmentioning
confidence: 99%
“…In injection molding, thermally induced residual stress caused by uneven cooling of polymer melt is the main one, 25 but the shear‐induced residual stress should not be ignored. The high‐speed shear flow in the injection molding process makes the molecular chains of the sub‐skin layer close to the mold surface highly oriented, and the relaxation of the molecular chains is limited by the core with a lower degree of orientation, resulting in residual stresses of skin stretching and core compression 26 . The shearing induced residual stress is of great significance for co‐injection, 27 three‐dimensional printing, 28 and surface wrinkle patterns 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Meanwhile, process simulation utilizing thermoelastic or thermo-viscoelastic models was performed to calculate residual stress due to the thermal skin-core effect. [5][6][7][8] However, these process simulations utilized material models (e.g., composite stiffness and shrinkage strain) developed based on many assumptions. This was mainly because conventional thermal analysis techniques utilized for material property determination had relatively slow cooling (SC) rates and direct determination during fast cooling (FC) ( > À10 C/min) was difficult.…”
Section: Introductionmentioning
confidence: 99%